PENGEMBANGAN BAHAN AJAR SASTRA ANAK BERBASIS LOKAL DAN BERPIKIR KREATIF SISWA - Alim, Abdul; Nahdi, Khirjan; Nursaly, Baiq Rismarini (SEBASA Jurnal Pendidikan Bahasa dan Sastra, 2022)
This study aims to develop local-based children's literature teaching materials and students' creative thinking skills and to describe creative thinking skills through local wisdom-based on children's literature teaching materials. This research is a development research. This study develpos the of children's literature teaching materials based on local wisdom and creative thinking that is adopted from the ADDIE development model which consists of the Analysis, Design, Development, Implementation, and Evaluation stages. The study was carried out on a small scale and a large scale by conducting validation first, namely: 1) linguist validation, the score obtained was 26 in the interval (23 < X (29) with the category "Good" an average of 74; 2) expert material validation, the score obtained is 51 in the interval X > 50. with the category "Very Good" an average of 85; 3) designexpert validation, the score obtained is 65 at interval X > (59) with an average of 95. The research instruments used were student learning outcomes tests, student response questionnaires, and observation sheets. Data analysis was carried out by converting quantitative data to qualitative data using a scale of five. Analysis of student learning outcomes test data was carried out by determining the percentage of minimum completeness criteria. This research produces children's literature teaching materials based on local wisdom and creative thinking for V (fifth) grade students very suitable category to use.Keywords: Teaching Materials, Children's Literature, Local Wisdom, Critical Thinking